Malta : 2020 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2020)
This 2020 Article IV Consultation focuses on Malta's near and medium-term challenges and policy priorities and was prepared before coronavirus disease 2019 became a global pandemic and resulted in unprecedented strains in global trade, commodity and financial markets. Pursuing structural reforms is expected to help sustain Malta's growth performance while promoting social inclusion. The focus should continue to be on encouraging female and elderly participation in the labor market, upskilling the labor force and stimulating innovation. Moreover, to safeguard the business climate, remaining governance shortcomings should be addressed without delay, including by stepping up the fight against corruption and by increasing the efficiency of the judicial system while ensuring its independence. Improving access to affordable housing remains a key priority in support of greater inclusion. It is imperative to maintain gradual consolidation to ensure a balanced structural budget excluding proceeds from the Individual Investor Program. The IMF staff suggests continuing addressing infrastructure needs while upgrading public investment efficiency. Improve fiscal risk analysis and management.